Pengaruh Pupuk Organik Cair Nanas dan NPK Mutiara terhadap Pertumbuhan Bibit Kakao - Kornelius, Amos; Fathillah, Syarief; Sundari, Sundari (Universitas Lambung Mangkurat, 2025)
This research aims to observe the effects of liquid organic fertilizer derived from pineapple extract and NPK Mutiara fertilizer on cocoa seedling growth (Theobroma cacao L.). The study used a factorial Randomized completely Block Design (RCBD) with 12 treatment combinations consisting of variations in pineapple concentration and NPK doses. The first factor was the concentration of pineapple, applied in four levels: p1 (pineapple extract 10 ml + 875 ml water), p2 (pineapple extract 20 ml + 900 ml water), p3 (pineapple extract 30 ml + 925 ml water). The second factor was the dose of NPK Mutiara, applied in four levels: n0 (no fertilizer/control), n1 (NPK 30 g/polybag), n2 (NPK 40 g/polybag), and n3 (NPK 50 g/polybag). The results showed that the application of pineapple and NPK Mutiara had no significant effect on the growth of cocoa plants, including parameters such as plant height, number of leaves, and stem diameter. Additionally, there was no significant interaction between pineapple and NPK Mutiara on any of the growth parameters observed.Kata kunci: NPK, Pineapple POC, Cocoa